Association of HIV and highly active antiretroviral therapy with clinical and biochemical indices among women with pre-eclampsia. Issue 3 (September 2016) - Maharaj, Niren R.; Moodley, Jagidesa; Chuturgoon, Anil
Abstract: Objective: To determine whether clinical and biochemical features associated with pre-eclampsia are significantly altered among women with HIV infection taking highly active antiretroviral therapy (HAART). Methods: A prospective observational cohort study was conducted between July 2013 and September 2014 at Prince Mshiyeni Memorial Hospital, Durban, South Africa. Women with and without pre-eclampsia and HIV infection were enrolled at booking and followed up until delivery. Specific demographic data, clinical features, laboratory indices, and complications were analyzed. Results: Of 193 participants, 98 had pre-eclampsia (45 [45.9%] with HIV infection). There were no significant differences in clinical features and laboratory indices among the study groups except for γ-glutamyl transferase levels, which were significantly higher among women with pre-eclampsia and HIV infection (26.9 ± 40.9 U/L) than among those with pre-eclampsia but no HIV infection (17.1 ± 14.0 U/L; P = 0.001). Perinatal and maternal complications were similar, and there were no maternal deaths. Conclusion: Clinical features, laboratory indices, and complications among women with pre-eclampsia and HIV infection taking HAART were similar to those among women with pre-eclampsia without HIV infection. Current guidelines remain appropriate; however, frequent hepatic function tests should be conducted.